Brain Gym: Pseudoscientific Practice - Kroeze, Kevin; Hyatt, Keith J.; Lambert, M. Chuck (Journal of the American Academy of Special Education Professionals, 2016)
There is an abundance of scams and pseudoscientific practices promising seemingly magical cures for whatever ails a person. A short viewing of late night television will readily reveal a whole host of scams that may be more effective at relieving the viewer of the cash in his or her pocket than alleviating any unwanted symptoms. Unfortunately, ineffective practices are not only advertised on late night television, sometimes, children who are compelled to attend school are forced to participate in practices that waste valuable instruction time. This paper will provide a brief review of Brain Gym which is one commercial program used in schools in over 80 countries under the assumption that it will improve student learning and a whole host of other skills, without actually teaching the skills. There is no quality empirical evidence supporting this claim, yet schools continue to expend valuable time and fiscal resources on such programs.